Experimental study of mechanical and durability properties in hybrid binary and ternary fiber-reinforced ECC - Kouhiazar Tulun, Mahdi; Sobhani, Jafar; Mirhosseini, Seyyed Mohammad; Zeighami, Ehsanollah; Basiri, Mohammad Reza (Frontiers in Built Environment, 2025)
This study develops innovative hybrid fiber-reinforced Engineered Cementitious Composites (ECC) to advance sustainable construction materials. By incorporating ternary fiber systems (steel, synthetic, PVA) with supplementary cementitious materials (GGBFS, silica fume), the composites achieved significant enhancements: a 40% increase in compressive strength (94.8 MPa), 31% higher tensile strength (8.99 MPa for S10F20P2), and 20% improved flexural toughness (120 N.mm for S20F10P2), while limiting crack widths to ∼60 μm. Durability tests revealed low water penetration (3.5 mm), reduced chloride ingress (87 coulombs), and 4.4 g/m2 mass loss during freeze-thaw cycles. The integration of industrial byproducts reduced CO2 emissions by 338.2 kg/m3, demonstrating dual mechanical and environmental advantages. These results highlight the potential of ternary hybrid fiber systems for high-performance, eco-friendly concrete overlays, bridging material innovation with sustainable construction practices.